Son of God : Divine Sonship in Jewish and Christian Antiquity. - Allen, Garrick V. (Penn State University Press, 2019)
"An interdisciplinary exploration of the diverse discourse on divine sonship in ancient Jewish and Christian literature. Authors focus on a range of issues including messianism, deification, eschatological figures, Jesus, interreligious polemics, and the Roman and Jewish backgrounds of early Christian writers and the authors of the Dead Sea Scrolls"--Provided by publisher.